Growth responses of Sorghum bicolor (L.) Moench to arbuscular mycorrhizal fungi under simulated nitrogen deposition (Bangladesh Journal of Botany, 2021)
Anthropogenic nitrogen (N) deposition leads to a dramatically increase in biologically available N in many ecosystems, which can change the symbiotic relationship between AMF and host plants. However, how and to what extent exogenous N-induced AMF could affect plants remains poorly understood. In this work, mycorrhizal growth responses of Sorghum bicolor to AMF under simulated N deposition were conducted in a glasshouse experiment. Results demonstrated that AMF elevated the growth performance and nutrient uptake (N, P) of S. bicolor at almost all treatments, although mycorrhizal colonization decreased with N addition. In addition, mycorrhizal response (MR) showed identical trend of first fall and then increase, and the lowest value was at the N1 treatment. The present study provided the first pot-based evidence that AMF can alleviate the mischief induced by high N addition, implying that AMF has a considerable significance in the farmland ecosystem under anthropogenic N deposition.Bangladesh J. Bot. 50(3): 933-938, 2021 (September) Special